THE RECYCLING BEHAVIOR OF ROMANIAN CONSUMERS - Mirela-Cristina VOICU (Challenges of the Knowledge Society)
For any of us, protecting the environment should no longer be an optional activity, taking into account the negative effects of the environmental degradation that is becoming increasingly acute these days. Yet a positive attitude toward protecting the environment is still lacking for many of us, not to mention the lack of positive behavior in this direction. As the field of environmental protection requires a multidisciplinary approach, the marketing also contributes to the achievement of sustainable economic development in our country, especially through the researches carried out on consumers ecological behavior. Both the business environment and public organizations require reliable information about the determinants of consumers' environmental behavior. One aspect of this ecological behavior is the recycling behavior. Given that the need to meet the European recycling standards is becoming increasingly stringent, it is also necessary to know all the factors that can determine an appropriate environmental behavior. In this context, the following paper reveals some important aspects regarding the current situation of the recycling activity in Romania together with the characteristics of the recycling behavior of Romanians that require a specific marketing activity conducted in this field.